2010
DOI: 10.1128/aac.01730-09
|View full text |Cite
|
Sign up to set email alerts
|

The 6-Aminoquinolone WC5 Inhibits Human Cytomegalovirus Replication at an Early Stage by Interfering with the Transactivating Activity of Viral Immediate-Early 2 Protein

Abstract: WC5 is a 6-aminoquinolone that potently inhibits the replication of human cytomegalovirus (HCMV) but has no activity, or significantly less activity, against other herpesviruses. Here we investigated the nature of its specific anti-HCMV activity. Structure-activity relationship studies on a small series of analogues showed that WC5 possesses the most suitable pattern of substitutions around the quinolone scaffold to give potent and selective anti-HCMV activity. Studies performed to identify the possible target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 40 publications
2
42
0
1
Order By: Relevance
“…We previously observed that WC5 is able to inhibit the IE2-dependent transactivation of two E genes of HCMV, i.e., UL112-113 and UL54, both in transfected cells and in the context of viral infection (31). Thus, to gain further insights into the mechanism of this inhibitory activity, we wished to identify the minimal portion of an E gene promoter activated by IE2 still sensitive to WC5 inhibition.…”
Section: Wc5 Does Not Affect Ie2 Dimerization and Its Interaction Witmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously observed that WC5 is able to inhibit the IE2-dependent transactivation of two E genes of HCMV, i.e., UL112-113 and UL54, both in transfected cells and in the context of viral infection (31). Thus, to gain further insights into the mechanism of this inhibitory activity, we wished to identify the minimal portion of an E gene promoter activated by IE2 still sensitive to WC5 inhibition.…”
Section: Wc5 Does Not Affect Ie2 Dimerization and Its Interaction Witmentioning
confidence: 99%
“…We previously observed that WC5 interferes with the transactivating activity of IE2 on two HCMV E gene promoters (31). Since IE2 regulates gene expression by both protein-protein interactions and direct binding to specific DNA sequences within E-responsive promoters (10), we first wished to determine whether the inhibitory effect of WC5 might be due to interference with two protein-protein interactions that are required for the transactivating activity of IE2, such as the interaction with itself and with cellular TBP.…”
Section: Wc5 Does Not Affect Ie2 Dimerization and Its Interaction Witmentioning
confidence: 99%
See 1 more Smart Citation
“…The EGFP-expressing cell lines show a specific and inducible dose-and time-dependent EGFP response to either HCMV infection or constitutive IE2 expression that can be visually assessed by fluorescence microscopy or evaluated by automated fluorometry (8). The reliability of these reporter cell lines for assessing virus-inhibitory effects in concentration-and time-dependent fashions after HCMV infection or IE2 transfection has been demonstrated by treatment with fomivirsen, an antisense oligodeoxynucleotide designed to block IE2 expression (8,9), and with WC5, a novel 6-aminoquinolone endowed with potent inhibitory activity for HCMV replication (10). Thus, these EGFP-based cell lines can be exploited as a tool to screen antiviral compounds that specifically target IE2 expression and/or function.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of K5 derivatives on HCMV attachment were analyzed as previously described (20). Briefly, 100 PFU of HCMV AD169 and various concentrations of K5 derivatives or heparin as a control were added to HFF monolayers prechilled at 4°C and incubated for either 2 or 4 h at 4°C.…”
Section: Compoundsmentioning
confidence: 99%